Study on Role of Private Sector Enterprises in Indian Economy: The Contribution of Private Sector Enterprises in the Growth of the Indian Economy (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Private sector enterprises have come to occupy a significant position in the Indian economy. They have helped in capital formation, reduction in concentration of economic power and removal of regional imbalances. They have been acting as a model employer, producing wide variety of products, developing necessary skills and technical know-how, reducing imports and increasing exports, and encouraging ancillary industries and generating surpluses for further development of economy. Serious gaps in the economy particularly in the fields of heavy industry such as manufacturing of steels, heavy machine tools, heavy electrical equipment, exploration and refining of oil, chemicals, fertilizers and indigenous production of defence equipment have been overcome through private enterprises. Thus, private sector enterprises have great economic importance for a developing country like India.